The relationship between protein and mrna expression of transcription repressor dream, c-fos and prodynorphin in modulating pain responses induced by formalin in the rat spinal cord. - Long, Idris (2011)

(untitled)
Protein Downstream Regulatory Element Antagonist Modulator (DREAM) bertindak sebagai penindas transkripsi bagi gen c-Fos dan prodynorphin yang terlibat dalam proses kesakitan.